'This Community Which Nobody Can Define': Meanings of Commonwealth in the Late 1940s and 1950s. Issue 3 (4th May 2019) - Prior, Christopher
ABSTRACT: Assessments of early postwar understandings of the power and potential of the Commonwealth have suggested the body either failed to shield the British public from a sense of national decline or that it comforted them that there was no need to worry about decolonisation because the organisation enabled the maintenance of British authority by other means. However, historians and political scientists who provided public comment on the present and future of the body in the late 1940s and 1950s complicate such assessments, wracked as they were by a profound uncertainty over what the Commonwealth could achieve. Their sense of uncertainty was not derived from a pessimistic reading of the tangible events and processes of the period that we might today assume blunted commentators' faith in Commonwealth cohesion, such as Britain's relationship with Europe, neutralism, apartheid, or even Suez. Instead, uncertainty over the Commonwealth's capacity to realise a latent potential supposedly rooted in its members' willingness to work together was rooted in something more elemental, namely sustained uncertainty regarding the nature of the body's connections and functions. The body was judged an abstraction, a nascent and unparalleled experiment whose bonds were extensive yet impossible to measure. Its perceived opacity rendered it neither a cause for concern nor a salve to a wounded British morale.